1997
DOI: 10.1152/ajpheart.1997.273.5.h2200
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of spontaneous baroreflex by antisense c-fosoligonucleotide treatment in the NTS of the rat

Abstract: We evaluated the hypothesis that basal Fos protein at the nucleus tractus solitarii (NTS), the primary terminal site for baroreceptor afferents, exerts a tonic inhibitory modulation on the spontaneous baroreceptor reflex (BRR) control machinery, which is responsible for beat-to-beat regulation of resting systemic arterial pressure (SAP). In adult male Sprague-Dawley rats anesthetized and maintained with pentobarbital sodium, microinjection bilaterally into the caudal NTS of a 15-mer antisense oligonucleotide t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Three 15-mer phosphorothioated c-fos oligonucleotides (Quality System, Taipei, Taiwan) were used, [22][23][24] including a key antisense oligonucleotide (ASON1) that targets against a region of the c-fos mRNA that flanks the initiation codon (5Ј-129 to 143-3Ј) and a corresponding sense (SON) and a scrambled (ASON2) c-fos oligonucleotide. Each oligonucleotide was microinjected bilaterally, at a volume of 50 nL, into the NTS (nϭ25 to 30 animals per group) under pentobarbital anesthesia (50 mg/kg IP) 24 hours before the experimental sessions.…”
Section: Microinjection Of Test Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three 15-mer phosphorothioated c-fos oligonucleotides (Quality System, Taipei, Taiwan) were used, [22][23][24] including a key antisense oligonucleotide (ASON1) that targets against a region of the c-fos mRNA that flanks the initiation codon (5Ј-129 to 143-3Ј) and a corresponding sense (SON) and a scrambled (ASON2) c-fos oligonucleotide. Each oligonucleotide was microinjected bilaterally, at a volume of 50 nL, into the NTS (nϭ25 to 30 animals per group) under pentobarbital anesthesia (50 mg/kg IP) 24 hours before the experimental sessions.…”
Section: Microinjection Of Test Agentsmentioning
confidence: 99%
“…[21][22][23][24] A rabbit polyclonal anti-Fos antiserum (sc-52, 1:4000; Santa Cruz) was used, and Fos-like immunoreactivity (Fos-LI) was visualized by a Vectastain ABC kit (Vector). As a routine, sections from both SHR and WKY that received the same treatment schedule were processed together.…”
Section: Immunohistochemical Stainingmentioning
confidence: 99%
See 2 more Smart Citations
“…s the principal terminal site of the primary baroreceptor afferents, 1 the caudal nucleus tractus solitarii (NTS) in the medulla oblongata has become a major focus in recent studies [2][3][4][5][6][7][8][9] on the anatomic and temporal specificity of Fos expression after cardiovascular perturbations. In terms of function, workers at our laboratory reported that both basal 6 and induced 4 Fos expression in the caudal NTS may represent an early step in the cascade of intracellular events that leads to long-term inhibitory modulation of baroreceptor reflex (BRR) response.…”
mentioning
confidence: 99%